A usage-based alternative to "lexicalization" in sign language linguistics. Issue 1 (4th February 2019) - Lepic, Ryan
Abstract : The usage-based framework considers linguistic structure to be emergent from how human languages are used, and shaped by domain-general cognitive processes. This paper appeals to the cognitive processes of chunking, entrenchment, and routinization to explore a usage-based alternative to the structuralist notion of lexicalization, as it has traditionally been used in sign language linguistics. This exploration shows that chunking, entrenchment, and routinization are useful for re-contextualizing three "lexicalization" phenomena sign language linguistics: multiword expressions, fingerspelled words, and morphologically complex signs. An advantage of the usage-based approach for linguistic theory and description is that it anticipates the existence of linguistic constructions that exhibit analyzable internal structure and holistic properties simultaneously. This alternate framing alleviates the burden for sign language linguists to determine whether or not linguistic constructions have become "lexicalized", and instead directs analysts to focus on the degree to which linguistic constructs are established in any language user's mental representation of their language.